The Age–Velocity Dispersion Relations of the Galactic Disk as Revealed by the LAMOST-Gaia Red Clump Stars - Sun, Weixiang; Shen, Han; Jiang, Biwei; Liu, Xiaowei (The Astrophysical journal, 2025)
Using nearly 230,000 red clump stars selected from LAMOST and Gaia, we conduct a comprehensive analysis of the stellar age–velocity dispersion relations (AVRs) for various disk populations, within 5.0 ≤ R ≤ 15.0 kpc and ∣ Z ∣ ≤ 3.0 kpc. The AVRs of the whole red clump sample stars are accurately described as σ v = σ v ,0 ( τ + 0.1) β v , with β R , β ϕ , and β Z displaying a global exponential decreasing trend with R , which may point to the difference in spatial distributions of various disk heating mechanisms. The measurements of β – R for various disks suggest that the thin disk exhibits a radial dependence, with a global exponential decreasing trend in β R – R and β Z – R , while β ϕ remains a nearly constant value (around 0.20 ∼ 0.25) within 8.5 ≤ R ≤ 11.5 kpc. The thick disk displays a global increasing trend in β R – R , β ϕ – R , and β Z – R . These results indicate that the thin disk stars are likely heated by long-term heating from giant molecular clouds and spiral arms, while thick disk stars are likely heated by some violent heating process from merger and accretion, and/or formed by the inside-out and upside-down star formation scenarios, and/or born in the chaotic mergers of gas-rich systems and/or turbulent interstellar medium. Our results also suggest that the disk perturbation by a recent minor merger from Sagittarius may have occurred within 3.0 Gyr.